L’immigration dans le roman actuel : enjeux sociaux et stratégies persuasives. Le cas de Soleil amer de Lilia Hassaine - Zdrada-Cok, Magdalena (Romanica Silesiana, 2023)
In her article, Magdalena Zdrada-Cok analyses the representation of immigration in Lilia Hassaine’s 2021 novel Soleil amer. She is concerned with argumentative and persuasive narrative strategies, the reterritorialization of immigration literature, and references to the realistic model of the novel.